2015
DOI: 10.1371/journal.pone.0132052
|View full text |Cite
|
Sign up to set email alerts
|

The Topoisomerase 1 Inhibitor Austrobailignan-1 Isolated from Koelreuteria henryi Induces a G2/M-Phase Arrest and Cell Death Independently of p53 in Non-Small Cell Lung Cancer Cells

Abstract: Koelreuteria henryi Dummer, an endemic plant of Taiwan, has been used as a folk medicine for the treatment of hepatitis, enteritis, cough, pharyngitis, allergy, hypertension, hyperlipidemia, and cancer. Austrobailignan-1, a natural lignan derivative isolated from Koelreuteria henryi Dummer, has anti-oxidative and anti-cancer properties. However, the effects of austrobailignan-1 on human cancer cells have not been studied yet. Here, we showed that austrobailignan-1 inhibited cell growth of human non-small cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…Here we show that cell cycle was arrested in G2/M phase, and this was observed from 8 h to 48 h of treatment at a 1.25 U/mL concentration. There are several agents, such genistein [ 64 ], austrobailignan-1 [ 65 ], and curcumin analog WZ35 [ 66 ], that can also cause an arrest in the G2/M phase of the cell cycle followed by cell death induction. Although a recent publication of our research group showed that I-CRP does not affect cell cycle in bone marrow cells of mice treated with I-CRP [ 11 ], here we show that in cervical cancer cells it induces cell cycle arrest in G2/M phase, uncovering a different effect in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that cell cycle was arrested in G2/M phase, and this was observed from 8 h to 48 h of treatment at a 1.25 U/mL concentration. There are several agents, such genistein [ 64 ], austrobailignan-1 [ 65 ], and curcumin analog WZ35 [ 66 ], that can also cause an arrest in the G2/M phase of the cell cycle followed by cell death induction. Although a recent publication of our research group showed that I-CRP does not affect cell cycle in bone marrow cells of mice treated with I-CRP [ 11 ], here we show that in cervical cancer cells it induces cell cycle arrest in G2/M phase, uncovering a different effect in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Topoisomerase inhibitors have been reported to induce capase-2 mediated DNA damage (Perchellet et al, 2004;Hua et al, 2006;Tomicic and Kaina, 2013;Wu et al, 2015). Topoisomerase inhibitors have been reported to induce capase-2 mediated DNA damage (Perchellet et al, 2004;Hua et al, 2006;Tomicic and Kaina, 2013;Wu et al, 2015).…”
Section: Dronedarone Downregulates the Expression Of Topoisomerase IImentioning
confidence: 99%
“…DNA damage can also result from topoisomerases dysfunction, which causes single-and double-strand DNA cleavage. Topoisomerase inhibitors have been reported to induce capase-2 mediated DNA damage (Perchellet et al, 2004;Hua et al, 2006;Tomicic and Kaina, 2013;Wu et al, 2015). Therefore, it was of interest to investigate the involvement of topoisomerases in dronedaroneassociated DNA damage.…”
Section: Dronedarone Downregulates the Expression Of Topoisomerase IImentioning
confidence: 99%
“…Several other aryltetralin lignans with alternative substitution patterns on the aryl rings have also been identified in nature (e.g., 3-6). [4] Interestingly,investigations into the bioactivities of these lignans have suggested that subtle changes in the substitution patterns of the aromatic rings could significantly affect the microtubule depolymerizing activity and therapeutic window of the scaffold. [4b,d,e] Them edicinal importance of this natural product family has spurred numerous chemical approaches, [5,6] including arecent Pd-catalyzed C À Harylation strategy to 1 by Maimone and co-workers.…”
mentioning
confidence: 99%